The role of selected mechanisms of innate immunity in the pathogenesis of diabetes - Trojanowska, Paulina; Chrościńska-Krawczyk, Magdalena; Trojanowska, Alina; Tywanek, Ewa; Wronecki, Jakub; Łuczyk, Robert Jan (Journal of Education, Health and Sport, 2021)
Understanding the important role of the non-specific immune response in protecting the body against the development of numerous diseases has become partially possible after the discovery of several classes of pattern recognition receptors (PRR), such as Toll-like or NOD-like receptors. A group of cytoplasmic proteins called the inflammasome, which detect PAMP and DAMP through the PRR receptors, is able to activate pro-inflammatory cytokines and trigger an acute inflammatory reaction both in the extracellular and intracellular space. Low-grade systemic and local inflammation contributes to the development and progression of various conditions, including autoimmune and metabolic diseases, such as diabetes, metabolic syndrome and atherosclerosis, which until recently were not even considered inflammatory diseases. This review will discuss the role of innate immunity in the development of type 1 and type 2 diabetes, focusing on the role of specific innate immunity receptors and insulin resistance involved in these diseases pathogenesis.